2015
DOI: 10.1007/s10815-015-0599-7
|View full text |Cite
|
Sign up to set email alerts
|

Why more is less and less is more when it comes to ovarian stimulation

Abstract: It is suggested to aim at the retrieval of around eight to ten eggs. Mild stimulation should be the common practice for IVF. In cases where more than ten ova are retrieved or high E(2) levels are reached, either intentionally or unintentionally, "freeze-all policy" should be considered and embryo transfer (ET) done in a subsequent natural cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
1
19
0
1
Order By: Relevance
“…This was observed in several studies, who found the lower implantation rate in high estradiol level condition during IVF ET cycle [10] [14] [15]. However, the difference in pregnancy results was not the primary goal of this study.…”
Section: Discussionsupporting
confidence: 50%
“…This was observed in several studies, who found the lower implantation rate in high estradiol level condition during IVF ET cycle [10] [14] [15]. However, the difference in pregnancy results was not the primary goal of this study.…”
Section: Discussionsupporting
confidence: 50%
“…More "mild" ovarian stimulation during IVF cycles has several benefits, including decreased incidence of ovarian hyperstimulation syndrome (OHSS), decreased frequency of multiple gestations, decreased rates of aneuploidy, lower cost, and improved access to IVF treatment [19]. Milder stimulation protocols have been associated with better implantation and pregnancy rates despite a lower number of oocytes retrieved [19]. Multiple mechanisms to explain this paradox that less oocytes may yield improved IVF outcomes have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms to explain this paradox that less oocytes may yield improved IVF outcomes have been proposed. Elevated E2 and P4 levels seen with conventional IVF protocols may be associated with direct embryo toxicity and diminished endometrial receptivity, and as such have poorer IVF outcomes [19]. It has been suggested that elevated E2 may disrupt folliculogenesis and oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…This would result in embryo transfer only being performed if the endometrium has not been exposed to ovarian stimulation and is in developmental synchrony with the embryo. As a compromise approach to this problem, low-dose stimulation regimens have been developed in an attempt to minimize the adverse effects of more aggressive conventional controlled ovarian hyperstimulation [104].…”
Section: Suboptimal Endometrial Function As a Results Of Controlled Ovmentioning
confidence: 99%